ผลของการแคลไซน์โดโลไมต์ต่อไพโรไลซิสน้ำมันพืชใช้แล้ว - ฉัตทิตา อ้อยใจ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of this study is to prepare a catalyst from natural dolomite via thermal treating for pyrolysis of used vegetable oil in a batch micro reactor of 70 ml. The two level factorial experimental design was performed to investigate the factor which has an effect on liquid yield, naphtha fraction in liquid product and acid value of liquid product. The response surface methodology was used to define the optimum condition as well as the highest yield of naphtha, the lowest yield of long residue and small amount of acidity. The result show that the dolomite catalyst prepared from calcined dolomite at 800°C for 2 hours represents the lowest calcination temperature and the lowest calcination time to decomposition dolomite to MgO and CaO, and the dolomite catalyst in this condition gave the highest surface area that is suitable for use as catalyst on used vegetable oil pyrolysis. The optimum mathematical simulation shown that the condition reaction temperature of 450°C, initial hydrogen pressure of 1 bar, time of reaction at 60 minute and 2.50 %wt of dolomite catalyst gave 55.01 %wt of liquid yield, 42.00 % of naphtha and 8.00 % of long residue in liquid product and 0.50 mg KOH/g of acidity.